Development of Guided Inquiry-Based Worksheet as Teaching Materials on Elements, Compounds, and Periodic Table - Alti, Rahmi Mudia (JTK (Jurnal Tadris Kimiya), 2021)
The chemistry lecture at Universitas Nurtanio needs teaching materials innovation to increase students' activity and learning motivation. This research aims to develop worksheets on the material of elements, compounds, and the periodic table and determine the validity and practicality. The stages carried out in this study are the define, design, and development stages. The validity and practicality data analysis used the moment kappa (k) formula. The average validity and practicality are 0.87 and 0.77, respectively, with very high criteria. The validity and practical result indicate that a guided inquiry-based worksheet can be applied as teaching materials on elements, compounds, and the periodic table in lectures.